2019
DOI: 10.1002/jcop.22246
|View full text |Cite
|
Sign up to set email alerts
|

Developmental transitions during adulthood and neighborliness: A multilevel cluster analysis

Abstract: Neighborliness plays a critical role in promoting social integration, and is known to positively influence health and psychosocial adjustment. We examined variation in neighborliness based on developmental transitions as well as on the neighborhood context. We examined the direct and moderating role of neighborhood factors, to determine whether the neighborhood context modified the influence of developmental transitions on neighborliness. We analyzed data from a longitudinal study of Australian communities, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Kloos et al [20] used a cluster randomization algorithm to deliver an online positive psychology intervention to nursing home staff. Aiyer et al [21] proposed an analysis of psychological transition and neighbourhood relationships in adulthood using a multilevel clustering algorithm. Evidence was found for the direct effects of cluster membership and structural factors on neighbourhood relationships.…”
Section: Related Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Kloos et al [20] used a cluster randomization algorithm to deliver an online positive psychology intervention to nursing home staff. Aiyer et al [21] proposed an analysis of psychological transition and neighbourhood relationships in adulthood using a multilevel clustering algorithm. Evidence was found for the direct effects of cluster membership and structural factors on neighbourhood relationships.…”
Section: Related Researchmentioning
confidence: 99%
“…To test the effectiveness of the improved PCA-based K-means clustering algorithm, a comparison with the typical K-means [29] and multilevel clustering [21] was performed on an artificially simulated dataset. e CPU used for the experiments was an Intel(R) Core(TM) i7-3770 CPU @ 3.40 GHz, with 4 GB of RAM, a 64 bit WIN 10 Operating System, and a MATLAB 2016b software environment.…”
Section: Manual Dataset Validationmentioning
confidence: 99%
“…This is the motivation, namely for bacteria from the genera Geobacter and Shewanella to be the most investigated model microorganisms as biocatalysts in MFC. Recently, it was established that a new bacterial strain, Pseudomonas putida 1046 [14], is capable of expressing a cellular redox compound mediating the electron transfer through a polymer matrix at high positive poising potential, which indicated that the bacteria possess electrogenic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Neighborliness is a particular form of neighboring, and both neighboring and neighborliness are localized dimensions of more expansive terms of art such as social capital, social organization, and others. Neighborliness occurs when neighbors engage in warm, caring, and mutually supportive relationships and is an element of social integration (Aiyer, Zahnow, & Mazerolle, 2020). Although neighborliness occurs in a variety of venues, as used here the term refers to locality-based, reciprocal social support predicated on positive neighborly relations.…”
mentioning
confidence: 99%